Impact of total thyroidectomy on quality of life at 6 months: the prospective ThyrQoL multicentre trial. Issue 2 (February 2020) - Mirallié, E; Borel, F; Tresallet, C; Hamy, A; Mathonnet, M; Lifante, J C; Brunaud, L; Menégaux, F; Hardouin, J B; Blanchard, C; ,
Abstract : Objective: This study is to determine the impact of complications after total thyroidectomy on health-related quality of life (HR-QoL) and to identify significant predictive factors of HR-QoL changes. HR-QoL is usually impaired in patients with thyroid diseases compared to the general population. Thyroidectomy is largely performed in the case of benign thyroid benign and can be associated with long-term complications (vocal cord palsy, hypoparathyroidism). Design: The prospective ThyrQoL multicenter trial (NCT02167529) included 800 patients who underwent total thyroidectomy for benign or malignant non-extensive disease in seven French referral hospitals between 2014 and 2016. Methods: HR-QoL was assessed using the MOS 36-item short form health survey (SF-36) self-questionnaire with a 6-month follow-up. Results: We observed a significant improvement of HR-QoL 6 months after surgery ( P  < 0.0001). Postoperative complications were associated with a non-significant impairment of HR-QoL. In multivariable analysis, Graves' disease was associated with a significant improvement of HR-QoL (OR = 2.39 [1.49; 3.84]) and thyroid malignant disease with an impairment of HR-QoL (OR = 1.44 [0.99; 2.08]) after thyroidectomy. Conclusion: We observed a significant improvement of HR-QoL 6 months after total thyroid surgery for benign thyroid disease.